Knowledge, Attitude and Perceived Confidence of USIM Dental Graduates Towards Management of Medical Emergencies - Nor Azura Ahmad Tarmidzi; Nalisha Mohamed Ramli; Norashikin Amran; Husna Najihah Norazmi; Nur Saniah Mohd Arifin (USIM Press, 2024)
Vol. 8 No. 2 (2022)